Analisis Pengaruh Perubahan Arus Eksitasi Terhadap Tegangan Keluaran dan Daya Reaktif di PLTG Gilimanuk - Tama, Agi; Yulanda, Erik Agustian; Sunardi, Sunardi; Wirakusuma, Komang Adi; Laksono, Pranoto Budi (Universitas Pamulang, Prodi teknik Elektro, 2024)
One of the most important components of a power plant is the generator, the change in a load will affect the voltage of the generator. The excitation system also has the task of monitoring and controlling the output voltage of the generator, therefore the generator must be able to generate electrical power in accordance with the amount of load given. The purpose is to compare the results of EDS measurements with the results of the calculations obtained, which will be analyzed with the aim of minimizing the occurrence of interference with excitation and reactive power in the generator. The analysis shows that the largest excitation current is found at 21:00 setting the excitation current by 868 A, the resulting voltage is 16.0 kV, while from the calculation results of 15.8 kV, from the comparison of measurements with calculations having 0.2 kV or 200 V. At 09:00 with an excitation current of 778 A, with an anchor current of 7.9 kA the reactive power produced is 25 MVAR, while in the calculation of the reactive power obtained at 24.6 MVAR, in the measurement with the calculation has a difference of 0.4 MVAR or 400 kVAR. At 22:00 it gets a reactive power of 15 MVAR so that it produces a power factor of 0.96, while in the cosphi calculation which is obtained at 0.95. It can be concluded that the greater the excitation current, the generator output voltage will be large, if the excitation current is large, the reactive power will also be large, if the reactive power is large, it will cause cosphi to decrease because the reactive power is inversely proportional to cosphi which will later cause power losses.